Pengaruh Psikoedukasi Kesehatan Mental dan Pelatihan Relaksasi terhadap Literasi Kesehatan Mental Siswa SMA - Habib Alfian; Noer Suci Endah Puspitaningrum (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
Adolescent mental health is an important educational and public health concern, as this developmental stage involves complex physical, emotional, social, and psychological changes that may increase vulnerability to mental health problems. Mental health literacy is therefore essential to help students recognize psychological difficulties, reduce stigma, and apply appropriate coping strategies. This study aimed to examine the effect of mental health psychoeducation combined with relaxation training on mental health literacy among high school students in Gresik, Indonesia. A quantitative approach with a pre-experimental one-group pretest–posttest design was employed. The participants consisted of 54 high school students who completed all stages of the study, including screening, pre-test, intervention, and post-test. Initial mental health screening was conducted using the Mental Health Continuum–Short Form (MHC-SF), while mental health literacy was measured using the Mental Health Knowledge Questionnaire (MHKQ). The intervention consisted of psychoeducation on mental health, stress, and coping strategies, followed by simple deep-breathing relaxation exercises. The screening results showed that students were distributed across flourishing, moderate, and languishing categories, indicating varied levels of mental well-being. The results further indicated a modest increase in mental health literacy scores from pre-test (M = 13.31) to post-test (M = 13.94), accompanied by a positive shift in literacy categories, marked by a decrease in the low category and an increase in the good category. These findings suggest that psychoeducation combined with relaxation training can support the improvement of students’ mental health literacy, although the magnitude of change remains moderate. This study provides practical implications for schools in developing simple, applicable, and promotive mental health programs to strengthen students’ understanding of mental health and adaptive coping.